2011
DOI: 10.1002/jcla.20473
|View full text |Cite
|
Sign up to set email alerts
|

Serum paraoxonase and arylesterase activities in various forms of hepatitis B virus infection

Abstract: The aim of this study was to determine and evaluate the activity of paraoxonase and arylesterase enzymes in various clinical forms of hepatitis B infection and to investigate the correlation between these parameters and chronic disease course/fibrosis. Overall, 40 patients diagnosed as hepatitis B carriers (CIHBV), 40 chronic active hepatitis B (CAHBV) patients, and 40 healthy adults (control group) between 18 and 65 years of age were enrolled the study. Serum paraoxonase and arylesterase activities were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
2
14
0
2
Order By: Relevance
“…QS factors are secreted by Gram-negative bacteria in particular to regulate biofilm formation [118]. Paraoxonase activity is also decreased upon viral infection (for review, see [111]); this is reported for the hepatitis C virus [119], hepatitis B virus [120] or for the human immunodeficiency virus (HIV) [121]. PON1 was reported to participate in cholesterol efflux from the cell membrane to HDLs [122]; this may contribute to reduce the presence of cholesterol rafts that are necessary for viral infection.…”
Section: Focus On Hdl-bound Paraoxonasementioning
confidence: 97%
“…QS factors are secreted by Gram-negative bacteria in particular to regulate biofilm formation [118]. Paraoxonase activity is also decreased upon viral infection (for review, see [111]); this is reported for the hepatitis C virus [119], hepatitis B virus [120] or for the human immunodeficiency virus (HIV) [121]. PON1 was reported to participate in cholesterol efflux from the cell membrane to HDLs [122]; this may contribute to reduce the presence of cholesterol rafts that are necessary for viral infection.…”
Section: Focus On Hdl-bound Paraoxonasementioning
confidence: 97%
“…This enzymatic activity is important for the protection of the cells from oxidative damage for the lipid oxidation metabolism and for the innate immunity response. It is reduced during hepatitis virus B infection and correlates with the functional status of the liver [40]. The inhibition of adenosylhomocysteinase activity, obtained by adenosine dialdehyde, has been described as a potent inhibitor of vaccinia virus early protein synthesis and viral mRNA methylation, suggesting that adenosylhomocysteinase activity is important in the translation of viral proteins and virus replication [41].…”
Section: Gene Ontology and Pathway Enrichment Analysismentioning
confidence: 99%
“…22 ROS have been shown to be significant mediators of various inflammatory processes, such as otitis media, maxillary sinusitis, adenotonsillitis, hepatitis, and Behçet's disease. 2,17,18,23,24 In COM patients, chronic inflammation in the middle ear is attributed to various mechanisms, such as the activation of macrophages and T-cells, the production of cytokines, and the presence of bacterial biofilms and endotoxins. 25,26 It is well known that each of these factors increases ROS production and causes tissue damage that should be eliminated by antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Some studies have shown that PON1 prevents the oxidation of cell membrane lipids induced by ROS, which can result in acute and chronic inflammation. 23,24 PON1 activity can be affected by inflammation. Serum PON1 activity is decreased in a series of pathological conditions, including coronary artery disease, hypercholesterolemia, type 2 diabetes, polycystic ovarian syndrome, and renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%